Building Integration of Solar Thermal Systems - Kalogirou, Soteris A. (My University, 2013)
With buildings accounting for 40% of the total primary energy requirements in EU, and the implementation of the Energy Performance of Buildings Directive (EPBD), developing effective energy alternatives is imperative. The EPBD requires that RES are actively promoted in offsetting conventional fossil fuel use. The use of RES in buildings is expected to rise dramatically in the next few years in view of the recast of the Directive, which specifies that the buildings should be nearly zero energy consumption. Meeting building thermal loads will be primarily achieved through an extensive use of solar thermal systems, following standard building energy saving measures. Solar thermal systems (STS) will have a main role as contribute directly to the heating and cooling of buildings and domestic hot water supply. The main problem that STS are facing today is that these are typically mounted on building roofing surfaces, creating aesthetic challenges and space availability issues. The solution to these problems would be the integration of STS into the traditional building envelope. The idea of integration is to replace the traditional building element with a STS one. This would also be a more economically viable solution. The possible problems that this integration could create are related to the rainwater sealing and protection from overheating, thus avoiding increased building cooling loads during summer. This paper aims to give a survey of possible STS integration on the building roofs and façades. The advantages of integration are quantified and suggestions are given to address the possible problems created.
Keywords: Solar thermal systems; Building integration; Façade integration; Roof integration